Pengaruh Metode Kerja Work From Home terhadap Tingkat Produktivitas Karyawan yang Dimoderasi oleh Gender - Probosari, Ninik; Rahmawati , Indah Laeli; Viyani, Ari Okta (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2023)
The Work from Home method of work is considered a relatively new adaptation for workers in Indonesia. This is because Indonesia only implemented it during the Covid-19 Pandemic. The pandemic period also brought problems to the level of employee productivity, which was moderated by gender roles. Data were collected from 60 employees who work with the Work From Home method. The results of this study indicate that the variable work method Work From Home has a significant positive effect on employee productivity, and gender moderates the relationship between the two, where Work From Home benefits female employees more than male employees.